Financial Sanctions and the Imports of Intermediate and Capital Goods in Iran: DID Method - Samira Heydarian; Mosayeb Pahlavani; Seyed Hossein Mirjalili (International Journal of Business and Development Studies, 2023)
During the last three decades, financial sanctions have been imposed on Iran by the United States, the European Union, and the United Nations Security Council. These sanctions have had various effects on Iran's economic sectors. This paper aims at estimating the effect of financial sanctions on the import of capital and intermediate goods in Iran, which was carried out for two independent time periods. The first period (2010-2013) includes multilateral financial sanctions, and the second period (2016-2019) includes multilateral sanctions and the withdrawal of the United States from the JCPOA. We examined the impact using the difference-in-difference (DID) method. The results of the first period indicate that the decrease in the imports of capital and intermediate goods in Iran depends more on the countries that "provided the sanctions plan" than the countries that did not provide the sanctions plan, because the coefficient of dummy variable for implementation in the random effects model is statistically significant. The negative effect of 0.007 on imports shows that the effect is weak, because this group of countries behaved differently. Since the implementation of multilateral financial sanctions in 2012, some countries such as Australia greatly reduced the export of capital and intermediate goods to Iran, but other countries such as Italy increased the export of capital and intermediate goods to Iran. In the second period, the random effects model is statistically significant. In this model, the negetive effect of 0.22 on imports indicates a significant effect. Therefore, the reduction of Iran's imports in this period depends more on the countries that provided the sanctions plan than the countries that did not provide the plan. Since the withdrawal of the United States from the JCPOA in 2018, countries such as Korea, Germany, Russia, UK and Italy reduced the export of capital and intermediate goods to Iran. The comparison of two independent periods indicates that in the first period, the major share of Iran's imports belongs to the UAE, and in the second period, it belongs to China. Turkey has been Iran's trading partner in both periods and since the imposition of sanctions, it has had an 8% share in the export of capital and intermediate goods to Iran, and with the withdrawal of the United States from the JCPOA, this share has increased to 13%.
Keywords: 330; financial sanctions; imports; capital and intermediate goods; difference-in difference method; Iran's economy